(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Treatment of patients with reactive arthritis (ReA) remains one of the most difficult problems of modern rheumatology. Its relevance is due to the progressive course of the disease, the severity of the lesion of the musculoskeletal system, the high incidence of lesions in people of working age, the early decline in functional abilities, the loss of professional and social skills, the difficulty of physical and psychological adaptation of patients to impaired motor functions, significant disability, which represent a serious general medical and social problem, leading to huge economic losses.